Application of lymphoplasmapheresis in the treatment of severe myasthenia gravis - Duan, Weiwei; Zhou, Hao; Dong, Xiaohua; Li, Bijuan; Li, Yi; Cai, Haobing; Zhou, Qian; Ouyang, Song; Yin, Weifan; Yang, Huan (Frontiers in Neurology, 2022)
Background Lymphoplasmapheresis (LPE) is a treatment that combines traditional plasma exchange and lymphocyte removal technique. It has been applied to treat a variety of autoimmune diseases, but its application value in the treatment of severe myasthenia gravis (MG) is not yet clear. Therefore, the aim of this study was to investigate the efficacy and safety of LPE in severe MG. Methods Clinical data of 123 severe patients with MG (Myasthenia Gravis Foundation of America Clinical Classification, Class IV) who received LPE treatment were included in a retrospective analysis. Efficacy was evaluated by the change of Quantitative Myasthenia Gravis score (QMGS) before and after treatment. Univariate and multivariate logistic regression analysis was used to explore clinical factors affecting efficacy. Results A total of 220 replacements were performed in 123 patients, with an average of 1.79 replacements per patient. The overall safety of LPE was good, and no serious adverse reactions occurred. After treatment, the mean QMGS of patients decreased significantly, from 23.40 ± 4.25 points before treatment to 17.93 ± 5.61 points after treatment, a decrease of 5.47 ± 4.16 points. 75.6% of patients experienced remission of clinical symptoms. During a 2-month follow-up of 64 patients, a progressive improvement in QMGS was found. Each muscle group involved in MG responded well to LPE treatment. In addition, LPE significantly reduced the levels of AChR-Ab and inflammatory cytokines in patients. Age ≥ 50 years and co-infection were unfavorable factors affecting the efficacy. Conclusions In this study cohort, LPE is safe for the treatment of severe MG and achieves good treatment outcome with fewer replacements. In patients with MG, the avoidance and timely control of infection are necessary. Our study provides a potential new treatment option for severe MG.